Scanning the body image of Job psychoanalytically - Zwan, Pieter van der (HTS teologiese studies, 2019)
It would seem that there has been a growing concern about the body during the composition of the Hebrew Bible, just as the body has awakened in the mind of the humanities during the last three to four decades in Western culture. Parallel to that has been a growing interest in psychological understanding often linked to the wisdom writings, and now again when the historical–critical approach has shown its limitations. The aim of psychoanalysing the body image of Job has several advantages: it allows the recipient to sense the body of the protagonist and so penetrate into the core of the narrative. Moreover, psychological sense can be made of the deeper meanings underlying certain body parts, which play a particularly important role for Job. In such a way, a network of subtexts can be accessed. This study will trace the image of Job’s body in the mind of the external world around him but more so in his own internal reality as depicted by the text. This will then constitute a body image which shifts amongst the characters and as the narrative develops. The clusters of attention imply the relations between the body parts in Job’s mind and suggest the tensions of his still unintegrated body image.